Subthreshold micropulse laser for adult onset Coats' associated exudative maculopathy. Issue 5 (September 2022) - Kumar, Ashok; Kumar, Poninder; Ambiya, Vikas; Mishra, Sanjay Kumar
Purpose: To report subthreshold micropulse laser as novel treatment modality for exudative maculopathy associated with adult Coats' disease. Methods: A 27-year old, young male presented with exudative maculopathy in adult onset Coat's disease with profound diminution of vision. Spectral domain-optical coherence tomogram (SD-OCT) revealed macular oedema with significant subfoveal hard exudates with massive subretinal exudations temporal to macula. He was planned for anti-VEGF injection to treat macular oedema in order to preserve vision but developed conjunctivitis which made any interventional procedure impossible. Patient was managed with subthreshold micro pulse laser using 532 nm green laser. Results: Patient had significant improvement in vision, resolution of macular oedema as well as hard exudate without any adverse effects on fovea. Conclusion: Novel treatment approach in form of subthreshold micro pulse laser could be an alternative treatment modality for exudative maculopathy associated with adult onset Coat's disease, especially in cases where other available interventional treatment options are not possible.